The Moises Padilla story the missing chapter - Milan, Wilfredo; Pesayco, Liberty; Hernandez, Antonio V.; Canseco, George; Directo, Tarhata M.; Adrales, Tom D.; Ramos, Pat; Cuenco, Apolina R.; Alonzo, Anthony; Solis, Charito; Alajar, Gina; Abuel, Tommy; et al. (Viva Home Entertainment, 1985)
Moises Padilla, an influential leader of Hukbalahap (a guerilla force) during World War II, no longer believes in their cause and runs for political office in his town. Conflict arises between Moises and the guerillas.